(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Water stress is a serious global issue regarding growth of agricultural crops and sustainable food production for the large population. In the present situation due to low rainfall and unavailability of advanced irrigation methods, water deficit stress is the most limiting factor decreasing crop production in many regions of the world. In this study, to assess the drought tolerance mechanism in cotton cultivars was monitored by drought- induced physio-biochemical changes. To assess the tolerance in cotton cultivars, a field experiment was conducted in split- plot design in which the main plot consists of irrigated and complete rainfed conditions as a stress and cotton cultivars arranged in the main plot as a subplot. The overall comparative analysis revealed that hybrid was superior over their parents under well-watered as well as in water deficit conditions in terms of chlorophyll content, wax content, accumulation of compatible solutes, photosynthesis rate, stomatal conductance, transpiration rate and yield parameters. The findings from the results indicate that under water deficit conditions plants having a different adaptive mechanisms for coping with the stress situation. So, some of the adaptive mechanisms such as accumulation of sugars, polyphenols, amino acids, non-enzymatic antioxidants, and wax deposition helps to maintain osmotic balance, to protect cellular macromolecules, to detoxify the cells, and to scavenge free radicals under water deficit condition.